Contemporary Oral Oncology : Rehabilitation and Supportive Care - Kuriakose, Moni Abraham (Springer International Publishing : Imprint: Springer, 2017)
This is the last of four volumes that together offer an authoritative, in-depth reference guide covering all aspects of the management of oral cancer from a multidisciplinary perspective and on the basis of a strong scientific foundation. This volume focuses on the topic of comprehensive rehabilitation and supportive care in oral cancer. The coverage includes the role of maxillofacial prosthodontics, advances in anaplastology techniques, and management of oral mucositis during radiation and chemotherapy. Holistic and supportive care approaches are discussed, and advice is provided on post-therapy surveillance and the use of different measures to assess quality of life. Nutritional evaluation and management and issues relating to healthcare economics are also considered. This volume will be of interest both to practicing specialists and to ancillary service staff involved in the care of oral cancer patients.
Keywords: Dentistry.; Medicine.; Oncology.; Oral surgery.; Maxillofacial surgery.; Surgical oncology.; elektronické knihy; electronic books